A Framework for Reduction of Violence against Girls in Secondary Schools of Mizoram - Mishra, Lokanath (International Journal of Psychosocial Rehabilitation, 2020)
There has been an increase in violence against women in Mizoram. It was not restricted to primary and secondary schools, but it was restricted to tertiary schools. Abuse against women is commonly under reported, misunderstood rarely discussed in schools. This qualitative work aimed at giving voice to children, women, parents and educators and thereby gaining insight into their views on girl violence in Mizoram high schools. This study aims at identifying and classifying the reasons of violence against girls in and around Mizoram high schools& establishing a mechanism for reducing violence against girls in Mizoram high schools. The study adopted a mixed approach and qualitative methodologies to investigate the meaning, dynamics and practices of girl violence in secondary schools. For the analysis, multi-stage Stratified sampling procedures have been adopted. The sample consisted of four districts, forty secondary schools, two hundred students (girls), teachers / parents, eight NGO workers and four government officials. For this research piece, the researcher uses both primary and secondary data. The respondents of study highlighted harmful effects of girl violence. Any kind of physical, emotional or mental abuse of schoolgirl is likely to increase her low educational profile, make them less and less available to schools or families, denying her right to education & de-motivated for class or homework. A framework has been developed to reduce violence against girls in Mizoram high schools.